SOCIAL AND PROFESSIONAL ASPECTS OF STUDENTS FORMING COMPETENCE IN HEALTH-SAVING - Serykh, A.B.; Mychko, E.I.; Yakybovskaya, A.E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the features of the formation of students' health protection competence in the context of social and professional problems. Methods and structure of the study. Empirical work was carried out on the basis of the Baltic Federal University. A diagnostic study was conducted with first and fourth year students using the questionnaire method, questionnaires "Index of attitudes towards health and a healthy lifestyle", "Attitudes towards health", which allow measuring the formation of structural components of the health saving competence. Results and conclusions. The results of the diagnostics made it possible to note common features in the formation of the cognitive and emotional components. The indicators of the formation of the behavioral component reflected irregular activity in maintaining a healthy lifestyle in the majority of respondents. The peculiarities of the formation of students' health saving competence are determined by their attitude to health as a necessary condition for successful professional activity and unwillingness to make efforts in this direction.